Body segments cooperation during forehand stroke production in young and adult tennis players - Zusa, A.; Lanka, J.; Vagin, A.; Cicchella, A. (Journal of Human Sport & Exercise, 2015)
The purpose of the study was to investigate biomechanical characteristics of the forehand stroke production in adult and young tennis players, such as body segments cooperation, separation angle (x-factor) and max speed of a racquet. Kinematic data was collected with an optoelectronic motion capture system Qualisys. Participants in the experiment were 6 mid-level adult tennis players (age 19.5 ± 2.3 years, weight 66.8 ± 7.7 kg, height 170.5 ± 7.8 cm, sports experience 13.2 ± 1.7 years) and 4 young tennis players (age 11 ± 0.6 years, weight 43.5 ± 4.8 kg, height 156.3 ± 4.8 cm, sports experience 5 ± 0.5 years). The task of the motion was to carry out 3 forehand strokes for 3 times, the position of the feet and type of stance was not regulated. Results showed that racquet speed during forehand follow through phase, is significantly higher in adult players. Adult athletes have significantly higher x-factor values, which indicates that they more effectively implement muscle-tendon complex pre-stretching principle during backswing and forward swing phase. As well as adults, young tennis players also perform principle of sequential action of body segments during the stroke production, according to their technical skills and level of training.